Debt Management and the Developing Nationts Economy: A Stochastic Optimal Control Analysis - Osu, Bright O.; Ubani, Sunday I. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper explores the usefulness of a stochastic optimal control analysis to discourage the less developed nations from borrowing funds from the more developed ones to service their investments (or worst still to service their yearly budget). The lenders of these funds are only interested in evaluating whether a borrower is likely to default. So they make policies to regulate and monitor the risk of an excessive debt that significantly increases the probability of default. The borrowing nation invests part of the loan into a cash account and a stock account in order to make more money. The net effect of the loan on the economy of the nation given that it must be repaid at a nominal interest rate compounded over a period of time is determined herein. Amazingly, this study discovered that as the debt is serviced by the borrower, the principal amount borrowed decreases as time increase but the interest rate (though fixed) increases as time increases, thereby sending the net worth of the borrowers’economy (income) towards a big crash.